Pengaruh Leverage, Profitabilitas, dan Ukuran Perusahaan terhadap Carbon Emission Disclosure pada Perusahaan Pertambangan di BEI Tahun 2019-2023 - Nenden Indah Nawangsih; Eksa Ridwansyah; Depita Anggraini (Komunitas Dosen Indonesia, 2025)
This research is motivated by increasing global warming due to high levels of greenhouse gases, some of which are produced from company operational activities. This research aims to obtain empirical evidence regarding the influence of leverage, profitability and company size on carbon emissions disclosure in mining sector companies. The research population consisted of 48 companies. The sample was selected using a purposive sampling method and obtained 10 companies which were observed for 5 years, so that the total data tested was 50 data. The data analysis methods used in this research include descriptive statistical analysis, classical assumption testing, multiple linear regression and hypothesis testing where data processing is assisted using SPSS 26 software. The results of this research prove that there is a positive influence between company size on carbon emissions disclosure. Meanwhile, leverage and profitability have no influence on carbon emissions disclosure. The implications of the results of this research indicate that company size can be a determining factor for companies to disclose their carbon emissions, so it is important for the government to consider policies that encourage transparency in environmental disclosure, especially for small and medium companies.